Differences in the Fatty Acid Profile, Morphology, and Tetraacetylphytosphingosine-Forming Capability Between Wild-Type and Mutant Wickerhamomyces ciferrii - Choi, Jun Young; Hwang, Hee Jin; Cho, Woo Yeon; Choi, Jong-il; Lee, Pyung Cheon (Frontiers in Bioengineering and Biotechnology, 2021)
One tetraacetylphytosphingosine (TAPS)-producing Wickerhamomyces ciferrii mutant was obtained by exposing wild-type W. ciferrii to gamma-ray irradiation. The mutant named 736 produced up to 9.1 g/L TAPS during batch fermentation in comparison with 1.7 g/L for the wild type. The highest production, 17.7 g/L TAPS, was obtained during fed-batch fermentation by mutant 736. Fatty acid (FA) analysis revealed an altered cellular FA profile of mutant 736: significant decrease in C16:0 and C16:1 FA levels, and increase in C17:1 and C18:2 FA levels. Although a significant change in the cellular FA profile was observed, scanning electron micrographs showed that morphology was similar between wild-type and mutant 736 cells. Genetic alteration analysis of eight TAPS biosynthesis–related genes revealed that there are no mutations in these genes in mutant 736; however, mRNA expression analysis indicated 30% higher mRNA expression of TCS10 among the eight genes in mutant 736 than that in the wild-type. Collectively, these results imply that the enhancement of TAPS biosynthesis in mutant 736 may be a consequence of systems level genetic and physiological alterations of a complicated metabolic network. Reverse metabolic engineering based on systems level omics analysis of mutant 736 can make the mutant more suitable for commercial production of TAPS.